Prevalence and treatment conditions for hypertension and dyslipidaemia complicated with systemic lupus erythematosus: A multi-centre cross-sectional study. (June 2021) - Saito, Mayu; Yajima, Nobuyuki; Yanai, Ryo; Tsubokura, Yumi; Ichinose, Kunihiro; Yoshimi, Ryusuke; Ohno, Shigeru; Sada, Ken-ei
Objective: This study aimed to assess the prevalence and actual treatment conditions for hypertension and dyslipidaemia complicated with systemic lupus erythematosus (SLE). Methods: This was a cross-sectional study. We established the lupus registry of nationwide institutions (LUNA), a multi-centre cohort of SLE patients in Japan. From February 2016 to July 2018, 597 SLE patients were registered in the LUNA. We evaluated the incidence of hypertension and dyslipidaemia and analysed the risk factors for hypertension and dyslipidaemia by logistic regression analysis. Results: Overall, 597 patients were enrolled in the study. The median age was 44 years, and 88.0% of the patients were female. Among all the patients, 92.9% used prednisolone. The prevalence of hypertension and dyslipidaemia was 43.9% and 54.7%, respectively. Among the patients receiving medication for hypertension, 24.7% exhibited insufficient control (systolic blood pressure >140 mmHg or diastolic blood pressure >90 mmHg), and among those receiving medication for hyperlipidaemia, 48.1% showed insufficient control (low-density lipoprotein cholesterol >140 mg/dL or triglyceride >150 mg/dL). The risk factors for hypertension were age, body mass index (BMI), disease duration, past maximum dose of prednisolone, and renal involvement, whereas those for dyslipidaemia were age and BMI. Conclusion: About half of the patients had hypertension or dyslipidaemia, and a considerable number of cases were poorly controlled despite medication. Our data suggest that physicians should treat SLE activity as well as its complications, especially the common risk factors for atherosclerosis.